Plausibility of menstrual cycle apps claiming to support conception - Freis, Alexander; Strowitzki, Thomas; Frank-Herrmann, Petra (Frontiers in Public Health, 2018)
Abstract The time of peak fertility in the menstrual cycle is limited and the day of ovulation varies, even in fairly regular cycles. Therefore, menstrual cycle apps indicating the fertile window for women trying to conceive must be quite precise. A deviation of some days may lead to focus on less- or non-fertile days and thus may be worse than random intercourse. The aim of our pilot study is to suggest a scoring system in order to rate cycle apps developed to indicate the fertile window and secondly to perform a pilot testing on 12 apps available in German and English language (6 calendar-based apps: Clue Menstruations- und Zykluskalender, Flo Menstruationskalender, Maya-Mein Periodentracker, Menstruationskalender Pro, Period Tracker Deluxe, WomanLog-Pro-Kalender; 2 calculo-theraml apps: Ovy and Natural Cycles; 4 sympto-thermal apps: myNFP, Ladycycle, Lily and OvuView). The calendar-based apps are compared to series of cycles with varying cycle lengths, the symptom-based apps are compared to cycles with known temperature rise, beginning and peak day of cervical secretions and clinical ovulation. The main criteria of our scoring system are: - What method/parameters is the determination of the fertile window based on? - What kind of studies exists concerning that underlying method/parameters? - What kind of studies exists concerning the app itself? - Is there a qualified counselling service? The calendar-based apps obtained zero points in our scoring system, as they did not comply with any of the seven criteria. Calculo-thermal apps revealed similar deficits predicting the most fertile days and obtained also suboptimal results. Lady Cycle obtained 20/30 points, myNFP 20/30 points, Lily 18/20 points, OvuView 10/20 points, Ovy 3/20 points and Natural Cycles 2/30 points. To conclude, a preselection of cycle apps along the state-of-the-art and according clear criteria has been suggested. Apps eligible for further studies are three of the tested symptothermal apps. The scientific evaluation of cycle apps depends on good prospective studies undertaken by researchers independent from the company.
Gesehen am 18.07.2019